ANALISIS BUTIR SOAL PEMELIHARAAN SASIS DAN PEMINDAH TENAGA KENDARAAN RINGAN KELAS XI SMK NEGERI 1 SEYEGAN - musyaffa, Dafiqi; Sukaswanto, Sukaswanto (Universitas Negeri Yogyakarta, 2022)
This study aims to determine the quality of the multiple choice items for the Final Assessment of Odd Semester Subjects for Chassis Maintenance and Light Vehicle Power Transfer for Class XI SMK Negeri 1 Seyegan for the 2020/2021 Academic Year. This research is a type of descriptive research with a quantitative approach. The data collection technique used is documentation to obtain data in the form of test question sheets, answer keys, and student responses. The data obtained were then analyzed using the program Anates Version 4.0.9 where the program will analyze the items in terms of validity, reliability, level of difficulty, discriminatory power, and effectiveness of distractors. The subjects in this study were all students of class XI Automotive Light Vehicle Engineering at SMK Negeri 1 Seyegan for the 2020/2021 Academic Year. The results showed that the quality of the multiple choice items for the Odd Semester Final Assessment of a total of 25 questions, there were 11 items (44%) in the very good category, 10 items (40%) in the good category, 2 items (8%) ) is in the sufficient category, 1 item (4%) is in the poor category, and 1 item (4%) is in the bad category. Overall, these items are of good quality and deserve to be tested on students.